USING COOPERATIVE LERNING MODEL- SNOWBALL THROW TO IMPROVE STUDENTS ENGLISH LEARNING OUTCOMES - Lanlan Muhria (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
The goal of this study was to see if a snowball throwing cooperative learning strategy could improve students' English learning outcomes in from of writing an advertisement. Classroom Action Research is the research method used in this study. The actions are divided into two cycles, each with four stages: preparation, implementation, observation, and reflection. The study was carried out at SMPIT Al Muhsinin with 24 students, 10 males and 14 females. Data gathering procedures are observations, interviews, assessments, and documentation. the findings of the research shows that snowball throwing cooperative learning strategy has a good influence on enhancing student learning outcomes, as seen by an increase in student learning completion in each cycle, which is 56.25 percent in cycle I and 81.25 percent in cycle II. As a result, the classical completion of pupil learning has been attained. The Snowball Throwing methodology, when used collaboratively, can boost students' learning motivation and cooperation when learning English.